Physician, heal thyself. Developing a hospital-based physician well-being committee. - Baird, N. (College of Family Physicians of Canada, 1995)
This article describes the development of a physician well-being committee at the Sir Mortimer B. Davis-Jewish General Hospital. It discusses the issue of physician stress, outlines the committee's mandate, and describes the various activities and services that were implemented.